CARD Y KRUEGER (1994) Y EL PROGRESISMO INTERVENCIONISTA CONTRA LA TEORÍA ECONÓMICA - Alonso Neira, Miguel Ángel; Gallego, Daniel José; Sánchez-Bayón, Antonio (REVISTA PROCESOS DE MERCADO, 2022)
MIGUEL ÁNGEL ALONSO NEIRADANIEL JOSÉ GALLEGOANTONIO SÁNCHEZ-BAYÓN